Gaming behaviour, coping, and self-regulation associated with online gaming addiction scores among school-aged children - Artika Nurrahima; Ah Yusuf; Ilya Krisnana; Moch. Abdul Mukid; Murniati Murniati (Pediomaternal Nursing Journal, 2026)
Introduction: Online gaming addiction causes various negative impacts on school-aged children. Online gaming addiction occurs due to the interaction of various factors. Objective: To examine the independent and incremental contributions of respondent characteristics, gaming behaviour, coping strategies, and self-regulation to online gaming addiction among school-aged children. Methods: A cross-sectional analytical design was used with 174 school-aged children who actively engaged in online games for the last 6 months, selected using a purposive sampling technique. Online gaming addiction was the dependent variable, while respondent characteristics, gaming behaviour, coping, and self-regulation were the independent variables. Data were collected using a demographic instrument, the Indonesian Online Game Addiction Questionnaire, the Brief COPE, and the SSRQ. Data were analyzed using hierarchical multiple linear regression. Results: The final hierarchical regression model explained 44.1% of the variance in online gaming addiction scores (adjusted R² = .392). Self-regulation significantly improved the model (ΔR² = .146, P-value < .001). Longer daily gaming duration (β = .230, P-value < .001) and greater weekly gaming frequency (β = .233, P-value < .001) were positively associated with online gaming addiction, whereas the formulating dimension of self-regulation was independently associated with lower addiction scores (β = −.258, P-value = .013). Conclusion: Gaming behaviour and self-regulation were independently associated with online gaming addiction among school-aged children. Promoting behavioural planning as a key component of self-regulation may help prevent online gaming addiction in this population. Keywords: behaviour; child health; internet gaming disorder; psychological factors